An IoT Wearable Smart Glove for Joint Flexibility Rehabilitation of Elderly Individuals - Nadarajan, Melina; Ahmad, Ida Laila (Evolution in Electrical and Electronic Engineering, 2024)
Due to their poor use and need for accurate placement and expertise, older individuals who are engaged in occupations requiring complex wrist movements find it tough to use current evaluation methods, particularly goniometers. The matter is made more complex by the lack of instruments that provide motivation. The goal of this work is to develop a cutting-edge smart glove with IoT capabilities that can monitor changes in joint flexibility resulting from stretching exercises. This cutting-edge glove will include a flex sensor that will allow users to easily monitor the development of their joints by examining a graph shown on their smartphone through an ESP32. The data on wrist motions, especially the angular velocity expressed in degrees and the related time needed to attain those angular velocities, will be shown on the graph. Users may evaluate the degree of joint flexibility acquired by continuously carrying out the advised stretching exercises each day by analyzing this graph. The smart glove will also include the capability to count and track the number of repetitions, ensuring users follow the advice given by healthcare experts. Anticipated results encompass enhanced availability of accurate measurements, increased exercise motivation, and thorough progress tracking for users and medical practitioners. The idea has importance for the aged as it addresses the shortcomings of existing methods and enhances general well-being by providing an accessible and inspiring means of maintaining independence and energy.